HUBUNGAN BEKERJA PART-TIME DENGAN AKTIVITAS BELAJAR MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS MULAWARMAN TAHUN AKADEMIK 2019/2020 - Noor Ellyawati; Sulfikar Sulfikar; Dina Destari; Vitria Puri Rahayu (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
This research seeks to determine the relationship of part-time working and learning activities of economics education students at Teacher Training and Education Faculty in Mulawarman University 2019/2020 academic year by using quantitative method. The study's population was drawn from all part-time economic education students, a total of 20 persons. Product moment correlation, validity and reliability tests, and questionnaires were utilized to obtain data from respondents.Â  According to the findings, part time working is related to the learning activities. The product moment correlation test showed part-time working has a significance level of 0.001 less than 0.005 and a value of rcount > rtable of 0.682 > 0.444, indicating that the correlation strength is "Strong." The findings also tell the proportion of the link between part-time working and learning activities is 0.68 or 68 percent. This indicates that 68 percent of part-time working is linked to learning activities, while the remaining 32 percent is linked to other factors. Looking for additional money is the most common indicator of part-time working, whereas expressing ideas is the most common indicator of learning activities. As a result, the value of r count > r table and Ha is accepted, implying that the relevance of the relationship between part-time working and learning activities is significant.Keywords: Part-Time Working, Learning Activities.